Surgeons Corner: Cavernoscopy for Rear Tip Extender Removal. Issue 8 (27th June 2018) - Thirumavalavan, Nannan; Hoover, Christopher R.V.; Gross, Martin S.
Abstract: Introduction: Cavernoscopy (using a cystoscope in the corpora) is traditionally used to retrieve rear tip extenders (RTEs) that are embedded at the time of removal or replacement of inflatable penile prostheses. Aim: To describe indications and techniques of cavernoscopy. Methods: We describe our preferred method of cavernoscopy to retrieve retained rear tips and present a thorough review of the literature regarding cavernoscopy. Main Outcome Measure: Ability of cavernoscopy to retrieve embedded rear tips without causing complications. Results: Cavernoscopy is feasible anecdotally in case reports, but other less-invasive methods of retrieving RTEs seem to have similar efficacy. Conclusion: Cavernoscopy is a technically feasible procedure that can be attempted as part of a stepwise algorithm for removing retained RTEs.